2005
DOI: 10.4067/s0034-98872005001000008
|View full text |Cite
|
Sign up to set email alerts
|

Influencia de la personalidad y el estilo de aprendizaje en la elección de especialidad médica

Abstract: (Rev Méd Chile 2005; 133: 1191-9).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
10
0
8
Order By: Relevance
“…[38] Previous studies have shown that learning style can change during an educational course. [11] Also, changes can be introduced to learning styles through practical learning. [39] However, the aim of the educational system is not changing teaching methods according to learners' learning styles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[38] Previous studies have shown that learning style can change during an educational course. [11] Also, changes can be introduced to learning styles through practical learning. [39] However, the aim of the educational system is not changing teaching methods according to learners' learning styles.…”
Section: Discussionmentioning
confidence: 99%
“…This is why different learners choose different careers or fields of study. [11] Kolb divided learners into four learning style groups, based on their preferred action at different stages of Kolb's cycle: diverging, converging, accommodating, and assimilating learners. [12]…”
Section: Introductionmentioning
confidence: 99%
“…Nesse estudo, os autores não fazem referência específica à especialidade de GO, mas à de Cirurgia, com a qual os ginecologistas poderiam ter maior aproximação. Observaram que os cirurgiões são geralmente do tipo ESTJ, pessoas práticas, decididas, realistas e diretas, voltadas para a implantação das decisões, focadas em resultados, cuidadosas com detalhes da rotina e gostam de passar rapidamente para a próxima etapa, pensando nos fatos de forma pragmática 19 . Ao apresentarem práticas de supervisão realizadas em diferentes especialidades, Kilminster et al 4 também sugeriram que parece haver características particulares de cada uma delas, mais uma vez sem dados específicos sobre GO.…”
Section: Discussionunclassified
“…Conocer los estilos de aprendizaje de sus estudiantes debe ser una prioridad de la Facultad de Ciencias Médicas de la Universidad Nacional de Asunción a fin de asegurar que sus modelos educativos, planeamientos y guías docentes incluyan el conocimiento acabado de los estilos posibles. Esto es crucial en el contexto que tienen los estilos de aprendizaje en la educación médica y, principalmente, en la elección futura de la especialidad y la satisfacción y eficiencia de sus estudiantes y graduados (41,42).…”
Section: Discusionunclassified